Evaluation of a biopsy technique of the epiphyseal plate radius of mules with angular deformity of surgical type : case study (2015)
ABSTRACT: eight mules with angular limb deformity (ALD) type carpus varus and carpus valgus were studied. Objective: to evaluate a biopsy technique of the distal growth plate of the radius using a Jamshidi needle. Methods: thirteen limbs with ALD were biopsied immediately before undergoing corrective surgery. The site of biopsy depended on the severity of ALD and surgical technique. The samples were preserved and processed for histopathological study. Results: of all biopsies evaluated, only three were successfully obtained. Conclusions: the biopsy technique used was not efficient (23% success rate), however it allowed us to describe the physeal dysplasia in mules with ALD. Our findings agree with those previously described in horses.